2018
DOI: 10.1152/ajprenal.00370.2018
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of complement 3 in the salt-sensitive hypertension by activation of renal renin-angiotensin system in spontaneously hypertensive rats

Abstract: We previously showed that complement 3 (C3) is highly expressed in mesenchymal tissues in spontaneously hypertensive rats (SHR). We targeted C3 gene by zinc-finger nuclease (ZFN) gene-editing technology and investigated blood pressure and phenotype in SHR. Blood pressure was measured by tail-cuff and telemetry methods. Histology and expression of liver X receptor α (LXRα), renin, Krüppel-like factor 5 (KLF5), and E-cadherin were evaluated in kidneys. Mesangial cells (MCs) were removed from glomeruli from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…A major involvement of the renin-angiotensin system during HE-aHUS has been demonstrated in the stroke prone spontaneously hypertensive rat model. 21 Interestingly, C3 is involved in the phenotype of this model, 22 and renin has been shown to cleave C3, an effect inhibited by a direct renin inhibitor. 23,24 Renin-angiotensin system activation is also correlated with hemolysis in HE patients.…”
Section: Discussionmentioning
confidence: 87%
“…A major involvement of the renin-angiotensin system during HE-aHUS has been demonstrated in the stroke prone spontaneously hypertensive rat model. 21 Interestingly, C3 is involved in the phenotype of this model, 22 and renin has been shown to cleave C3, an effect inhibited by a direct renin inhibitor. 23,24 Renin-angiotensin system activation is also correlated with hemolysis in HE patients.…”
Section: Discussionmentioning
confidence: 87%
“…Hypomethylation of the TLR2 gene increased the risk of essential hypertension in the Chinese population [42]. It was shown that C3 is highly expressed in mesenchymal tissues in spontaneously hypertensive rats (SHR) [43] and increased C3 induces salt-sensitive hypertension in SHR [44]. In [45] was discussed that IL-13 was involved in the induction of pulmonary hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…Complement activation was also seen in an angiotensin II-induced hypertension model in mice. In spontaneously hypertensive rats, C3 deficiency could abolish salt-sensitive hypertension [18], indicating that C3 is critical involved in hypertensioninducing pathways. However, these effects can also be mediated further downstream in the complement cascade.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat DOCAsalt hypertension model, glomerular C3 deposition was increased in DOCA-salt rats and decreased by antihypertensive therapy, that is, spironolactone and triple therapy with hydrochlorothiazide, reserpine, and hydralazine [13]. Recent studies using preclinical models of hypertension suggested a role of complement in the pathogenesis of hypertension [14] mediated by different immune cells like macrophages and regulatory Tcells (Tregs) [15][16][17] and activation of the renin-angiotensin system leading to phenotypic changes in vascular smooth muscle cells [18]. The detailed role of renal complement deposition in the development of elevated BP is still unclear.…”
Section: Introductionmentioning
confidence: 99%